Water Table Control Model for Maize Cultivation of C Typology Land on Tidal Lowland Reclaimed Area of South Sumatra, Indonesia - Imanudin, Momon Sodik; Madjid, Abdul; Bakri, Bakri; Armanto, Mustika Edi; Priatna, Satria Jaya; Warsito, Warsito; Mardiansa, Edwin (JOURNAL OF TROPICAL SOILS, 2025)
Tidal lowland productivity in type C is still low. Most of them have only been able to cultivate rice twice a year. The third cultivation of corn often fails due to a lack of water. The research objective is to determine an operational model for water management in the field for maize cultivation at several planting times. Model area is conducted at a tertiary block of reclaimed tidal lowland, Telang Jaya Village Primer 8 Delta Telang I, of  Banyuasin District. There are three planting times treatments: the fourth week of April, the second week of June, and the first week of July, 2021. A water management model was applied to control the drainage system, in which the water level in the tertiary channel is maintained at a depth of 50 cm. When groundwater drops below 70 cm, and there is no rain, pump irrigation is provided. Results of the field experiment showed that the maize crop showed similar growth quality at each phase. Land with a planting period of June and July still requires water addition using pump irrigation. It was applied on 14th and 18th August. Moreover, the maize cultivated at the end of April did not require pump irrigation. All treatments have generally similar production with an average magnitude of 8.0 Mg ha-1. The highest production is 8.73 Mg ha-1, which is planted in the first week of July.